Gap between willingness and behavior in the vaccination against influenza, pneumonia, and herpes zoster among Chinese aged 50–69 years. (2nd September 2021) - Lu, Xinyue; Lu, Jia; Zhang, Liping; Mei, Kewen; Guan, Baichu; Lu, Yihan
ABSTRACT: Background: Vaccination uptake of influenza vaccine, 23-valent pneumococcal polysaccharide vaccine (PPV23) and herpes zoster vaccine (HZV) remains low among Chinese aged 50–69 years, posing a significant public health concern. This study's aim is to determine the gap between the vaccination willingness and uptake. Research design and methods: We conducted a face-to-face questionnaire survey among the persons aged 50–69 years in 13 communities in Shanghai in November–December 2020 to measure vaccination willingness, vaccine price sensitivity, vaccination service accessibility, and vaccine hesitancy. Then, we explored the factors influencing the vaccination uptake using a structural equation model. Results: Vaccination willingness was 70.5% (self-paid influenza vaccine), 79.4% (free PPV23 for local persons), 54.7% (self-paid PPV23 for non-local persons), and 16.6% (self-paid HZV); however, actual uptake was 10.8% (influenza vaccine), 11.0% (free PPV23), and 2.5% (self-paid PPV23). Moreover, vaccination uptake was strongly influenced by service accessibility (β = 0.941), followed by willingness (β = 0.201), price sensitivity (β = −0.188), and medical history of vaccine-preventable diseases and underlying diseases (β = 0.176). Related knowledge (β = 0.017) and vaccine hesitancy (β = −0.003) affected the uptake indirectly. Conclusion: There is a gap between the vaccination willingness and uptake in Chinese elderly. It warrants specific measures, including increasing service accessibility and reforming payment mechanism, to bridge the gap.